Tendencia frente a la práctica del sexting en 50 jóvenes entre 14 Y 16 años de la Institución Educativa Pablo Emilio Camacho Perea de Zarzal, Valle - Agudelo Arroyave, María del Mar (Universidad Antonio Nariño, 2022)
Sexting, sending and receiving sexual and erotic content in the form of text messages, images and videos, is one of the new forms of interaction among young people, but it is a dangerous practice as it involves physical and emotional risk, and in some cases until death. Therefore, the objective of this study was to characterize the impact of this practice on the social relations of adolescents in grade 9 of the Efraín Varela Vaca Educational Institution, Pablo Emilio Camacho Perea (Zarzal, V). For the design of the study, a descriptive observational study was carried out. how much and for this analysis, 45 questionnaires were distributed to the same number of students included in the study population. The data was tabulated in Microsoft Excel, from which frequencies, percentages, etc